The discourses - Machiavelli, Niccolo (London : c)
Proposes a system of government that would uphold civic freedom and security by instilling the virtues of active citizenship, and that would also encourage citizens to put the needs of the state above selfish, personal interests. Ambitious in scope, but also pragmatic, this work creates a modern theory of republic politics.
Keywords: Historiography -- .Rome; Political science -- Early works to 1800.